Visibilización de los colectivos sociales en Diario La Prensa, periodo enero-junio de 2022 - Valarezo Flores, Edwin Fernando (2025)
This research analyzes the visibility of social collectives in the newspaper “La Prensa” of Riobamba during the period from January to June 2022, employing a mixed approach that combines content analysis of the journalistic notes issued by the media during the study period with interviews of editors and specialists in the subject. The results show limited coverage, with only 25 publications addressing issues related to social collectives, where feminist, indigenous, and citizen collectives are the most represented. Coverage was primarily focused on local issues, with 72% of publications targeting this audience, and an informative approach predominated. In conclusion, there is a partial and superficial representation of the collectives, which limits their presence in the public agenda. As recommendations, there is a need to strengthen the training of journalists in inclusion and human rights issues, encourage direct contact with representatives of the collectives, and diversify the formats and informative approaches to achieve a more equitable and representative coverage